The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1074/jbc.275.21.16023
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Nrf2 Coordinately Regulates a Group of Oxidative Stress-inducible Genes in Macrophages

Abstract: Electrophiles and reactive oxygen species have been implicated in the pathogenesis of many diseases. Transcription factor Nrf2 was recently identified as a general regulator of one defense mechanism against such havoc. Nrf2 regulates the inducible expression of a group of detoxication enzymes, such as glutathione Stransferase and NAD(P)H:quinone oxidoreductase, via antioxidant response elements. Using peritoneal macrophages from Nrf2-deficient mice, we show here that Nrf2 also controls the expression of a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
978
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,319 publications
(1,022 citation statements)
references
References 42 publications
32
978
1
2
Order By: Relevance
“…Many studies have reported that HO-1 expression is mainly regulated by Nrf2-dependent ARE activation in several cell types. [44][45][46] Studies of the ectopic expression of Nrf2 and siRNA constructs of Nrf2 and HO-1 further confirmed that the protective effect of flunarizine is indeed through Nrf2/HO-1 in cisplatin-treated cells. Our results also suggest that the AREdriven upregulation of HO-1 gene expression after treatment with flunarizine was mediated by nuclear translocation of Nrf2, not by de novo synthesis of Nrf2 in HEI-OC1.…”
Section: Discussionmentioning
confidence: 82%
“…Many studies have reported that HO-1 expression is mainly regulated by Nrf2-dependent ARE activation in several cell types. [44][45][46] Studies of the ectopic expression of Nrf2 and siRNA constructs of Nrf2 and HO-1 further confirmed that the protective effect of flunarizine is indeed through Nrf2/HO-1 in cisplatin-treated cells. Our results also suggest that the AREdriven upregulation of HO-1 gene expression after treatment with flunarizine was mediated by nuclear translocation of Nrf2, not by de novo synthesis of Nrf2 in HEI-OC1.…”
Section: Discussionmentioning
confidence: 82%
“…The Bach1-Maf heterodimers bind to the Maf recognition element (MARE) in the regulatory region of its target genes [72,[74][75][76][77]. MAREs are found in the regulatory regions of genes involved in heme metabolism, such as oxidative stress response genes, globin genes, heme oxygenase-1 and erythroid-specific ALAS [72,[78][79][80][81]. It has been suggested that the transcription of genes possessing MAREs is regulated via a balance between transcriptional activation and repression [22,80].…”
Section: The Transcriptional Repression Activity Of Bach1 Is Negativementioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that plays a central role in the regulation of antioxidant and phase 2 detoxifying enzymes and related proteins [27,28]. In the cytoplasm, Keap1 (Kelchlike ECH-associated protein 1) binds to Nrf2 and facilitates its ubiquitination and thereby prevents its translocation to the nucleus.…”
Section: Introductionmentioning
confidence: 99%